Osteocalcin in human breast milk over the course of lactation - Prosperi, Olivier; Hanusch, Beatrice; Naber, Sophia; Lücke, Thomas; Sinningen, Kathrin (Frontiers in Endocrinology, 2025)
BackgroundBreast milk is the best nutrition for newborns. Its composition is dynamic and adapted to the newborn’s individual needs. A variety of bioactive compounds, including bone-related molecules, have been described in breast milk. Osteocalcin (OCN) is a small non-collagenous, bone-derived protein. In its carboxylated form (cOCN) it plays a crucial role in bone metabolism and calcium homeostasis. The undercarboxylated form of osteocalcin (ucOCN) is suggested to have endocrine functions such as influencing neurotransmitter synthesis and glucose homeostasis. This study aimed to analyze whether the bone-related proteins cOCN and ucOCN are present in breast milk at different time points of the lactation phase and whether the amount is affected by lifestyle factors, such as dietary behavior, physical activity, BMI, age, or number of parities.Methods98 mothers, aged 31.8 ± 4.7 years, participated in the study. Breast milk was collected at four points during the breastfeeding period (T1: 1–3 days postpartum (pp); T2: 7 days pp; T3: 14 days pp; T4: 3 months pp). Total protein, ucOCN and cOCN were analyzed by BCA (bicinchoninic acid) assay and enzyme immunoassay, respectively. Dietary habits, physical activity, and BMI were assessed.ResultsThe median concentration of cOCN in relation to the total amount of protein decreased only marginally during the breastfeeding period (T1: 0.068 [0.021-0.207] ng/mg protein; T4: 0.045 [0.026-0.196] ng/mg protein), with total protein concentrations in breast milk decreasing. In contrast, the relative ucOCN concentration in relation to the total protein concentration was twice as high in the colostrum (0.125 [0.043-0.223] ng/mg protein) compared to mature breast milk (0.055 [0.028-0.091] ng/mg protein). The concentration of ucOCN in colostrum from primiparous women (0.138 [0.041 – 0.342] ng/mg protein) tended to be higher than the concentration in colostrum of multiparous women (0.062 [0.034 – 0.151] ng/mg protein, p = 0.094). This also applied for the cOCN concentration. Other lifestyle factors, e.g., physical activity, BMI, or age showed no associations with ucOCN concentrations in breast milk.ConclusionThis study indicates that ucOCN and cOCN are components of breast milk. The function of both molecules in infants and mothers, still needs to be uncovered. Clinical Trial Registrationhttps://www.bfarm.de, identifier DRKS00023072.